2020
DOI: 10.1002/anie.202002300
|View full text |Cite
|
Sign up to set email alerts
|

A Memristive Element Based on an Electrically Controlled Single‐Molecule Reaction

Abstract: The exponential proliferation of data during the information age has required the continuous exploration of novel storage paradigms, materials, and devices with increasing data density. As a step toward the ultimate limits in data density, the development of an electrically controllable single‐molecule memristive element is reported. In this device, digital information is encoded through switching between two isomer states by applying a voltage signal to the molecular junction, and the information is read out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 39 publications
(16 reference statements)
0
41
0
Order By: Relevance
“…Recent experiments have shown that the conductance of single-molecule junctions can be markedly affected by the charging states of the bridging molecule. [17,18] Moreover, they proposed that repeating Im À À Au units are pulled out to bridge the junction during the elongation corresponding to the low conductance features, which still calls for further verifications. Taken together, in order to gain a deep insight into the formation and conducting mechanism of imidazole-based molecular junctions, it is highly desirable to perform first-principles theoretical calculations taking explicitly into account the atomic and charging states of the central imidazole molecule in the junction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments have shown that the conductance of single-molecule junctions can be markedly affected by the charging states of the bridging molecule. [17,18] Moreover, they proposed that repeating Im À À Au units are pulled out to bridge the junction during the elongation corresponding to the low conductance features, which still calls for further verifications. Taken together, in order to gain a deep insight into the formation and conducting mechanism of imidazole-based molecular junctions, it is highly desirable to perform first-principles theoretical calculations taking explicitly into account the atomic and charging states of the central imidazole molecule in the junction.…”
Section: Introductionmentioning
confidence: 99%
“…A series of comparative experiments unambiguously reveal the elimination of the hydrogen atom, but strictly speaking, either an imidazole radical (Im) or an imidazole radical anion (Im − ) bridging the junction has not been clearly identified. Recent experiments have shown that the conductance of single‐molecule junctions can be markedly affected by the charging states of the bridging molecule [17,18] . Moreover, they proposed that repeating Im − −Au units are pulled out to bridge the junction during the elongation corresponding to the low conductance features, which still calls for further verifications.…”
Section: Introductionmentioning
confidence: 99%
“…Oligo(arylene ethynylene)s films consist of packed macromolecules with π-conjugated backbone thus exhibit high fluorescence emission which can be altered upon binding of an analyte molecule. OArEs films are an excellent materials for detection of amino acids [61], bacteria [79,80], explosives [34,81,82,85], pH [84], inorganic acids [83], gas [86], digital information [87] or chemicals [88,89]. Usually, the detection of an analyte is based on fluorescence changes, its enhancement or quenching upon binding of the sensed molecule.…”
Section: Oligo(arylene Ethynylene)s Sensor Filmsmentioning
confidence: 99%
“…Oligo(phenylene ethynylene)-based sensors have been used to encode digital information [87]. The oligomers ( Table 1, no.…”
Section: Oligo(arylene Ethynylene)s Sensor Filmsmentioning
confidence: 99%
See 1 more Smart Citation